2017
DOI: 10.1002/cncr.31120
|View full text |Cite
|
Sign up to set email alerts
|

Hospital quality, patient risk, and Medicare expenditures for cancer surgery

Abstract: Total episode expenditures for cancer resections were lower when care was delivered at low-complication, high-quality hospitals. Expenditure differences were particularly large for high-risk patients, and this suggests that the selective referral of high-risk patients to high-quality centers may be an effective strategy for optimizing value in cancer surgery. Cancer 2018;124:826-32. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…26 In a separate study, Shubeck et al noted increased expenditures ($20,992 vs $24,406 for colectomy, $21,282 vs $27,638 for lung resection, and $35,149 vs $45,731 for pancreatectomy, p < 0.0001 for all) and had higher rates of readmission (12% vs 13% for colectomy, 12% vs 13% for lung resection, and 22% vs 25% for pancreatectomy) among low quality hospitals performing surgery, compared with high quality hospitals. 3 Collectively, data from the current study as well as these previous reports strongly suggest that higher costs do not necessarily translate into higher quality. 27 In fact, we noted that higher payments for rescuing patients from complications after liver and pancreas surgery were not associated with better clinical outcomes.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…26 In a separate study, Shubeck et al noted increased expenditures ($20,992 vs $24,406 for colectomy, $21,282 vs $27,638 for lung resection, and $35,149 vs $45,731 for pancreatectomy, p < 0.0001 for all) and had higher rates of readmission (12% vs 13% for colectomy, 12% vs 13% for lung resection, and 22% vs 25% for pancreatectomy) among low quality hospitals performing surgery, compared with high quality hospitals. 3 Collectively, data from the current study as well as these previous reports strongly suggest that higher costs do not necessarily translate into higher quality. 27 In fact, we noted that higher payments for rescuing patients from complications after liver and pancreas surgery were not associated with better clinical outcomes.…”
Section: Discussionsupporting
confidence: 63%
“…Substantial variation in Medicare payments for surgical episodes across hospitals nationwide has been previously reported. 3,21,22 For example, Miller et al reported that Medicare episode payments for colectomy and back surgery varied by 49-130 percent across hospitals in the US. 23 In a separate study, Pradarelli et al analyzed variations in Medicare payments for rescuing patients from surgical complications (cost-of-rescue) after four common procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACOs must know who their beneficiaries are if they are to optimize surgical costs, in particular if they wish to prospectively identify high-cost surgical patients for intervention. 33,34 Recently, prospective beneficiary assignment has been implemented, but its effects remain to be seen. In particular, there may be important interactions between beneficiary assignment to an ACO and hospital ACO affiliation that can ultimately influence quality and cost of surgical care.…”
Section: Discussionmentioning
confidence: 99%
“…In more than 100 simultaneous transplantations, Campos Hernández et al 4 have described 65.5% of cases with postoperative complications. Banga et al 5 [6][7][8][9][10][11] . However, the relationship of postoperative complications in SPKT with hospitalization cost has only been studied in literature by two groups and in a limited way [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%